The Cultural Significance in Greeting Practices in Belo Dialect of the Bima Language - Alek, Alek (Register Journal, 2019)
Indonesia is the home to a vast array of cultures and many unique languages that are the mother tongues of these various islands and cultural groups. One of these is Bima language. Greeting systems and the address of personal names has long been a question of great interest in linguistic fields, especially sociolinguistic study. The main objective of the recent study was to answer some of the main issues as follows: (1) What are name variations in the greeting practices using in the Bima language? (2) How are the name variations applied in daily interactions of the Bima language? (3) Which syllables which are dominantly chosen in greeting terms? The results of my research will present the variations in the greeting system and address of personal names and their variety. Those variations are either at the beginning, the middle or the end of the syllables. However, none of the Bima people’s names begin with a consonant: “C, P, V, and X” as well as the vowel O.” it will also show that the variation of greeting practices and address of names applied in the daily interactions of the Bima language are different for men and women. The effort of maintaining the local style is essential to preserving and investigating as part of the national language because the position and function of the local languages are significant to the contribution and the progress and standardization of the national language. Keywords: Greeting practices, Bima language, and cultural significance